Thai classical dance exercise for fall prevention - Pittavat Leelapattana (2019)
© 2018, Medical Association of Thailand. All rights reserved. Background: Falls are one of the major causes of injury and loss of independence in the elderly and are significantly associated with increased morbidity and mortality. Balance impairment and muscle weakness are the most prevalent risk factors for falls in the elderly. Several kinds of therapeutic exercises have been demonstrated to reduce the risk of falls in older people. Thai classical dance uses key muscles of the upper and lower extremities to control body balance and to maintain an upright position. Thai classical dance exercise challenges key muscles, providing both muscle strengthening and balance training which can reduce the risk of falls, although those benefits have not yet been documented. Objective: To evaluate the efficacy of Thai classical dance exercise for fall prevention in the elderly using physical performance tests. Study design: Randomized controlled trial. Materials and Methods: A double-blinded randomized controlled trial was conducted at Ramathibodi Hospital during 2014 to 2015. Self-ambulatory older women were randomly assigned to one of two groups. The experimental group participated in daily 10 minute programmed Thai classical dance exercises; the control group participated in daily 10-minute sessions of arm swing exercise. Both groups participated in the exercise programs for 12 weeks. The primary outcome measure was improvement in physical performance as determined by standard tests including 3-meter tandem gait, timed up and go, and chair rise (sit and stand) tests. Physical performance was evaluated at baseline and after 4, 8 and 12 weeks of exercise. Analysis of variance was used to compare the outcomes between the two groups. Results: There were 19 participants in experimental group and 20 in control group with an average age of 66.4 and 66.9 years, respectively. After 12 weeks of exercise, the experimental group had significantly improved over baseline on the timed up and go test and on the tandem walk test (p = 0.002 and 0.001, respectively), and had also significantly improved on the timed up and go test compared to the control group (average 14.2±4.3 to 9.2±2.9 sec, and 13.0±3.8 to 11.2±4.3 sec, respectively; p-value = 0.0125). There was no difference in the chair rise test between the groups. Conclusion: Daily Thai classical dance exercise for one month is an efficacious way to improve physical performance in older women and to help reduce the risk of falls.